Bioacumulação de íons de Pb+² na macrófita Salvinia auriculata - Thomé, Luciara Ciane Port (2008)
In this work was carried out a study of the lead bioaccumulation process by living aquatic macrophytes Salvinia auriculata. Initially, they were performed toxicological and growing tests in order to determine the non-toxic lead concentration limits and the minimum amount of biomass for the lead uptake experiment duration. The bioaccumulation experiment was performed using young and healthy floating aquatic plants of species S. auriculata. Approximately 30 grams of S. auriculata were put in growing at several 8-L recipients containing 5 L hydroponics solution and a non-toxic lead concentration of 2 mg L-1, during 29 days in a greenhouse. For the lead uptake experiment, seven collection times were set up at intervals of 1, 2, 5, 8, 22 and 29 days, including the zero time and was measured the growing solution temperature and pH, and the solution volume was monitored and deionized water was added to compensate the losses by evaporation. In order to measure the total lead concentration accumulated in aqueous solution obtaining from roots and leaves and growing solution, a Synchrotron Radiation Total Reflection X-Ray Fluorescence technique was used. The lead removal factor by S. auriculata after 29 days, in experimental conditions, was around 87 %. Moreover, it was observed a strong reduction of 50 % of lead concentration in liquid phase and lead accumulation in roots after the first 24 hours of experiment, while there a constant lead concentration in roots after the second day, indicating the transport and accumulation of lead into the leaves. The lead adsorption experimental data by S. auriculata were modeling by the irreversible adsorption kinetic of Langmuir. In the model, the equation system was resolved by DASSL algorithm and the kinetic parameters were obtained and optimized by an objective function using a SIMPLEX algorithm. The adsorption rate constant (k) value was 0.12 L d mg-1 Pb+2 while the maximum lead contents (qmax) value in the biomass was 0.15 mg Pb+2 g-1. The aquatic plant S. auriculata can be a good alternative for effluent treatment through both bioadsorption and bioaccumulation mechanism. The process based on the Phytoremediation technique using aquatic plants have become a attractive economical process due to its easy applicability , low operational costs and high efficiency.